Cyclic response of rectangular RC columns retrofitted by hybrid FRP sheets. (December 2020) - Shin, Dong-Hyeon; Kim, Hyung-Joon
Highlight: To verify cyclic responses of RC columns retrofitted by HFRP sheets. To find out effects of numbers of HFRP sheet plies and wrapping lengths on the RC column retrofit. To develop analytical models properly capturing cyclic responses of HFRP retrofitted RC columns. Abstract: In an effort to enhance the seismic capacity of non-seismically designed reinforced concrete (RC) columns, this study proposes a retrofit method for non-seismically designed RC columns using hybrid FRP (HFRP) sheets consisting of glass and carbon FRPs. HFRP sheets can be installed for retrofitting the RC columns in a structure employing electric equipment such as metro stations or tunnels. With the assumption that the cyclic behavior of RC columns retrofitted with wrapping HFRP sheets is dependent on their numbers of plies and their wrapping lengths, full-scale cyclic tests with a total of five specimens were carried out to verify their seismic performance and to confirm the effects of HFRP sheets. In addition, this study aims to construct an analytical model to predict the cyclic behavior of HFRP retrofitted RC columns for more practical applications. The analytical model can properly capture the cracking and maximum strength with reasonable tolerance and also well simulate the hysteresis loops including pinching phenomenon as well as confinement effect of wrapping HFRP sheets. The BC specimen without employing HFRP sheets suffers the lowest inelastic deformation following the strength degradation with the early spalling of concrete cover. The test and analytical results present that wrapping HFRP sheets results in slight increase in the initial stiffness whereas cracking and maximum strength enhanced up to 15% since the HFRP sheet delay the crack propagation. The specimens wrapped with HFRP sheets develops the significant increase in the deformation capacities due to the increase in the confinement of concrete around plastic hinge regions. For the maximum deformation capacity of retrofitted RC columns, the number of plies of HFRP sheets wrapped at the expected plastic hinge regions is more influential than their length. The deformation capacity of RC columns wrapping two plies of HFRP are enhanced up to at least 2.1 times of that of a non-seismically design bare RC column.